2019
DOI: 10.1177/0032258x19836144
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the outcome of police safeguarding notifications to social services in South Wales

Abstract: In the UK, demand for the police has changed, with the majority of calls now vulnerability-related. Police safeguarding notifications (N=3,466) over a one-year period for a local authority in Wales were matched to social care records. Over half (57.5%) of notifications were referred to social services and only 4.8% received social service input (e.g. social worker intervention). Over a third of individuals had repeat notifications in the study year. Findings evidence high levels of police-identified vulnerabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…This article builds on and expands the focus of work that has sought to draw attention to the regressive consequences of purportedly progressive policies in relation to sex work and vulnerability across a range of legislative contexts (Munro and Scoular, 2012;Pheonix, 2012;Munro and Scoular, 2013;Brown and Sanders, 2017). In doing so, it contributes to wider discussions on the utilisation of harm reduction and vulnerability as concepts in the field of criminal justice and policing (Ford et al, 2019), and how they enable the increased criminalisation and exclusion of sex workers (Munro and Scoular, 2012: 31). By focusing on the Welsh context, it provides insights that contribute to a broader international analysis of the function of vulnerability in policing (Asquith et al, 2018), as well as the ability of criminal legal systems to ever be able to meaningfully protect sex workers (Stardust et al, 2021).…”
Section: Introductionmentioning
confidence: 93%
“…This article builds on and expands the focus of work that has sought to draw attention to the regressive consequences of purportedly progressive policies in relation to sex work and vulnerability across a range of legislative contexts (Munro and Scoular, 2012;Pheonix, 2012;Munro and Scoular, 2013;Brown and Sanders, 2017). In doing so, it contributes to wider discussions on the utilisation of harm reduction and vulnerability as concepts in the field of criminal justice and policing (Ford et al, 2019), and how they enable the increased criminalisation and exclusion of sex workers (Munro and Scoular, 2012: 31). By focusing on the Welsh context, it provides insights that contribute to a broader international analysis of the function of vulnerability in policing (Asquith et al, 2018), as well as the ability of criminal legal systems to ever be able to meaningfully protect sex workers (Stardust et al, 2021).…”
Section: Introductionmentioning
confidence: 93%
“…From a policing standpoint, this intervention would ensure that proper notifications are made to social services agencies and providers so that proper assistance is provided to vulnerable victims. This has proven to be effective in reducing repeat calls for service (Ford et al ., 2020). Evidence suggests that early intervention will provide better outcomes for children experiencing ACEs (Asmussen et al ., 2019).…”
Section: Viewing Crime As a Public Health Issuementioning
confidence: 99%
“…The UK's 'safeguarding' approach mandates the involvement of various government and non-government services (including the police) in the lives of people assumed to be at risk, particularly due to age and/or cognitive and physical disabilities. While the rhetoric of these approaches is to empower vulnerable people to 'live free from abuse, harm and neglect' (Care Quality Commission 2019), often disjointed interagency collaboration and austerity measures means that their needs are minimised, dismissed, or simply not addressed (Ford et al 2020). Ford et al found that while police consistently identify and respond to vulnerability-perhaps as a way to deflect the work necessary to respond to vulnerable people's needs onto other services-their referrals to those social services are often go unheeded.…”
Section: Vocal and Well-resourced Vulnerable Communities Are Most Capable Of Getting Their Concerns On The Agenda Often To The Detriment mentioning
confidence: 99%